Methods of Delivery of Medications for the Treatment of Oncological Diseases - Oltarzhevskaja, N.D; Krichevskij, G.E.; Korovina, M.A.; Shvets, V.I.; Kubatiev, A.A. (Biomedical Chemistry: Research and Methods, 2019)
The review focuses on the analysis of various methods of obtaining and applying therapeutic materials used for targeted drug delivery to the lesion site of cancer patients. Special attention is paid to creation of targeted drugs by using nanotransporters, obtained by dispersing lipids in water and, in particular, liposomes; efficiencyof such nanotransporters depends the nature of drugs introduced into them (cytostatics). The review also describes methods of targeted transport of cytostatics to tumor tissues. The use of hydrogel therapeutic compositions based on biopolymers polysaccharides for the targeted delivery of chemotherapy drugs introduced into them, allows to control the mass transfer rate of drugs to tumor and to create therapeutic materials with predetermined properties in terms of drug concentration in the lesion site and time prolongation, which reduces toxicity of the treatment and increase its effectiveness.